The Influence of Service Quality on Customer Retention (A Survey on Customers of Keziaspot East Jakarta) - Fadhilah, Azka; Purnomo, Margo; Purbasari, Ratih (Journal Research of Social Science, Economics, and Management, 2025)
The beauty industry in Indonesia has experienced significant growth, particularly post-COVID-19, with increasing demand for professional skincare services. However, maintaining customer retention remains a challenge for clinics like Keziaspot East Jakarta, which faces fluctuating repeat client rates due to inconsistent service quality. This research examines the influence of service quality on customer retention at Keziaspot, aiming to identify key areas for improvement. Using a descriptive-quantitative approach, data were collected from 80 respondents through surveys, measuring service quality (tangibility, reliability, responsiveness, assurance, empathy) and customer retention (financial benefit, social benefit, structural ties). Statistical analyses, including linear regression and normality tests, revealed a significant positive relationship (regression coefficient = 0.537, *p* = 0.001), with service quality explaining 77.6% of customer retention variance. Findings highlight reliability and empathy as critical drivers, while structural ties require enhancement. The research concludes that consistent service quality improvements—particularly in staff training, communication, and facility cleanliness—can strengthen retention. Practical implications include adopting integrated strategies like CRM tools and loyalty programs to foster long-term customer relationships. This research contributes to service quality theory and offers actionable insights for beauty clinics competing in Indonesia’s growing market.